Synthesis and characterization of manganese (II) complexes with N, O- donor schiff base / Norhafiza Roslan - Roslan, Norhafiza (Faculty of Applied Sciences, 2010)
Two Schiff base ligand has been synthesized by the condensation of salicylaldehyde with aniline and 1,2-diaminocyclohexane which produced p-benzalaminophenol [SBl] and N,N'-bis(salicylidene)cyclohexanediamine [SB2] respectively. The ligands were further synthesized with manganese (II) acetate which produced [Mn(II)SBl] and [Mn(II)SB2] complexes. These ligands and complexes were then characterized by elemental CHN analysis, FTIR, UV-Vis, ¹H-NMR and ¹³C-NMR spectroscopies. FTIR, UV-Vis, ¹H-NMR and ¹³C-NMR spectroscopic data revealed that the ligands acted as bidentate ligand for [SBl] and tetradentate ligand for [SB2]. While FTIR and UV-Vis spectroscopic data showed that the ligands from [SBl] and [SB2] were coordinated to Mn atom through both the azomethine N atoms and phenolic O atoms to become as their complexes.